The effect of wall temperature to the combustion of diesel/CNG mixture - Firmansyah, (Asian Research Publishing Network, 2016)
The stringent emission regulations and the need to increase fuel efficiency makes controlled auto-ignition (CAI) based combustion an attractive alternative solution to these issues. However, the combustion control is the main obstacle to its development. Fuel combinations with substantial different in reactivity such as diesel/compressed natural gas (CNG) shows desirable combustion output and demonstrate great possibility in controlling the combustion. This paper will discuss the control method of diesel/CNG (DCNG) mixture combustion with a variation of wall temperature. The experiment was done in a constant volume combustion chamber with both fuels were directly injected into the chamber. The wall temperature was varied from 45°C to 75 °C with an increment of 15°C. The increment of wall temperature reduces the combustion performance of DCNG. It is caused by slower combustion rate of DCNG that indicated by its long combustion duration. Regardless the combustion performance reduction, it was found that the combustion delay of DCNG was not affected by the wall temperature. © 2006-2016 Asian Research Publishing Network (ARPN).